Pengaruh Suku Bunga, Likuiditas, dan Bagi Hasil terhadap Deposito Mudharabah pada Bank Umum Syariah yang ada di Indonesia - Laily Nur Fitriana; Syaiful Syaiful (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine the influence of interest rates, liquidity, profit sharing on mudharabah deposits with independent variables, namely interest rates, liquidity and profit sharing. This research uses a quantitative approach and the sample used is 8 Islamic banks registered with the Financial Services Authority (OJK) the 2019-2021 period which was obtained through the purposive sampling method. The analysis technique used is multiple linear regression with the help of SPPS 25.0 for Windows. The research results show that the interest rate variable does not have a significant effect on mudharabah deposits, this is because increases or decreases that occur in a bank will not affect deposits, people who save their funds tend to see interest at the beginning which will provide big profits and feel more secure. The liquidity variable has a significant influence on mudharabah deposits because with increasing FDR, customers' expectations that the bank will earn greater profits makes them invest more in mudharabah deposits. The profit sharing variable shows that there is a significant influence on mudharabah deposits, this means that an increase in profit sharing will increase the number of mudharabah deposits in sharia banks. The greater the amount of profit sharing offered, the better.